Монгол Улсын Ерөнхийлөгч Н.Энхбаяр, Бүгд Найрамдах Казахстан Улсын Ерөнхийлөгч Н.Назарбаевын хамтарсан мэдэгдэл (Journal of International Studies, 2008)
English title: Joint declaration of the N.Enkhbayar, President of the Mongolia and N.Nazarbayev, President of the Republic of the Kazakhstan